2014
DOI: 10.1111/jvp.12125
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of marbofloxacin in pigs after intravenous and intramuscular administration of a single dose of 8 mg/kg: dose proportionality, influence of the age of the animals and urinary elimination

Abstract: The pharmacokinetics of marbofloxacin in pigs were evaluated as a function of dose and animal age following intravenous and intramuscular administration of a 16% solution (Forcyl®). The absolute bioavailability of marbofloxacin as well as the dose proportionality was evaluated in 27-week-old fattening pigs. Blood PK and urinary excretion of marbofloxacin were evaluated after a single intramuscular dose of 8 mg/kg in 16-week-old male pigs. An additional group of 12-week-old weaned piglets was used for the evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
44
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(51 citation statements)
references
References 14 publications
6
44
1
Order By: Relevance
“…The significant correlation between dose and AUC 24 (R 2 ϭ 0.9899) allows us to calculate the AUC 24 for other dosages. This phenomenon was confirmed in other research, i.e., for marbofloxacin PK in pigs within doses ranging from 4 to 16 mg/kg (26); however, our estimated PK parameters were somewhat different from those published previously for chickens infected by M. gallisepticum plus Escherichia coli (17). After i.m.…”
Section: Discussionsupporting
confidence: 81%
“…The significant correlation between dose and AUC 24 (R 2 ϭ 0.9899) allows us to calculate the AUC 24 for other dosages. This phenomenon was confirmed in other research, i.e., for marbofloxacin PK in pigs within doses ranging from 4 to 16 mg/kg (26); however, our estimated PK parameters were somewhat different from those published previously for chickens infected by M. gallisepticum plus Escherichia coli (17). After i.m.…”
Section: Discussionsupporting
confidence: 81%
“…The relative bioavailability obtained for marbofloxacin after p.o. application was 94.35 ± 8.90%, which is in between the bioavailabilities (91.50 ± 13.70% and 107.90 ± 13.40%) reported previously [22, 23]. In this study, higher intramuscular marbofloxacin bioavailability (more than 100%) may be because of the prolonged elimination half-lives after i.m.…”
Section: Discussionsupporting
confidence: 79%
“…The total body clearance of marbofloxacin decreases in older pigs [14], which may be the reason for the longer t 1/2λz reported here. Pigs used here were eight weeks old and younger than those used by Schneider et al [14].…”
Section: Discussionmentioning
confidence: 95%
“…The pharmacokinetics of marbofloxacin in plasma and urine has been studied in pigs under different administration routes [14], and it was shown that marbofloxacin is well absorbed with a bioavailability of 91.5% after intramuscular administration, and its body clearance rate decreases significantly with pig age after intravenous administration. Another study showed easy penetration of marbofloxacin into pig tonsils [19].…”
Section: Introductionmentioning
confidence: 99%